PERLINDUNGAN TERHADAP LESSEE USAHA DALAM PERJANJIAN SEWA GUNA SEBAGAI KONTRAK BAKU - sudjana, sudjana - (Res Nullius Law Journal, 2023)
This study aims to determine the clarity of existence (leasing) in agreement and leasing law in the perspective of standard agreements.The method of approach is juridical normative and the data is analyzed in a qualitative normative way to produce descriptive data based on the study of statutory norms.The results of the study show that leasing in treaty law has 2 (two) financing categories, namely finance lease (lease with option rights) and operating lease (lease without option rights). In contract law, the operating lease has the aspect of a lease agreement while the finance lease is more in line with the aspect of buying and selling, but each of these aspects compared to the financing category still has a difference. Whereas leasing in the standard agreement perspective applies in accordance with freedom of contract vide Article 1320 jo Article 1338 of the Civil Code as long as it does not lead to eliminating the responsibility of the business actor (exenorasi classula), but considering the lease agreement unilaterally determined by the lessor, the position of the lessee is still weak legal protection through legal action that can be carried out, for example filing a claim for compensation, costs and interest